The left atrial substrate plays a significant role in the development of complex atrial tachycardia in patients with precapillary pulmonary hypertension - Fingrova, Zdenka; Havranek, Stepan; Ambroz, David; Jansa, Pavel; Linhart, Ales (BMC cardiovascular disorders, 2019)
BACKGROUND: Atrial fibrillation (AF) and related atrial tachyarrhythmias (AT), including type I atrial flutter (AFL) are frequently observed in patients with pulmonary hypertension (PH). Their relationship to hemodynamic changes, atrial size, and ventricular function are still not fully verified. METHODS: We retrospectively studied hemodynamic data, echocardiographic findings and arrhythmia incidence in 814 patients with invasively diagnosed precapillary PH (aged 59 ± 14 years; 46% males). Patients with combined or post-capillary PH were excluded. RESULTS: AF / AT were identified in 225 (28%) of all the study population. Compared to the subgroup without arrhythmia, patients with AF / AT had elevated right atrial pressure (11 ± 5 vs. 9 ± 5 mmHg), wedge pressure (11 ± 3 vs. 10 ± 3), a more enlarged right atrium (50 ± 12 vs. 47 ± 11 mm) and an increased left atrial diameter in the parasternal long axis projection, p <  0.05 for all comparisons. In the multivariate model, the left atrial size, patient age, arterial hypertension, diabetes and type of PH were associated with AF / AT occurrence, p <  0.05. Patients with type I AFL were more frequently male (39 (80%) vs. 62 (42%)), were younger (61 ± 11 vs. 67 ± 10 years), had increased pulmonary artery mean pressure (50 ± 12 vs. 45 ± 12 mmHg), less advanced left atrial dilatation (38 ± 10 vs. 42 ± 7 mm), and a more enlarged right atrium (56 ± 12 vs. 48 ± 11) as compared to subjects with AF or other AT, p <  0.05. CONCLUSIONS: The evidence of elevated wedge pressure and the enlargement of the left atrium especially in patients with AF suggest a parallel involvement of the left atrial substrate in arrhythmia formation despite invasively confirmed evidence of purely isolated precapillary PH. Substantial differences were noticed between patients with type I AFL and the remaining patients with other arrhythmia types.
Keywords: Česká republika; Atrial Fibrillation; Aged; flutter síní; plicní hypertenze; hodnocení rizik; Aged, 80 and over; Atrial Function, Left; Retrospective Studies; lidé středního věku; senioři; Hypertension, Pulmonary; fibrilace síní; srdeční frekvence; lidé; Risk Factors; Adult; Incidence; Czech Republic; Middle Aged; dospělí; supraventrikulární tachykardie; Tachycardia, Supraventricular; Female; Risk Assessment; senioři nad 80 let; Atrial Flutter; Male; ženské pohlaví; Action Potentials; Heart Rate; Humans; mužské pohlaví; akční potenciály; prevalence; rizikové faktory; incidence; srdce - funkce levé síně; Prevalence; retrospektivní studie